The Syrian women between reality horizons - Mohammad, Osama; Dawood, Mariana (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
In most Arab countries, women have encountered some sort of sexual discrimination over many centuries. This is what distinguishes the cause of women and makes research in their status an important issue. In addition, the world is witnessing today a heated controversy about the role of women in society and the extent to which women are supposed to be engaged in the development and target sectors work process, and to what extent this engagement will affect the traditional role of woman as wife and mother. There are many studies and much research on the status of women and their problems and conditions with the aim of to enabling them. However there is still a lot to be done. All have stressed the importance of women’s empowerment and their active role in the development process, while current research seeks to find the criteria and factors that may help to achieve this empowerment in line with the reality and many responsibilities of Syrian women, the nature of our society with its traditions and customs. In Addition to the need to define the constraints and obstacles that hinder the empowerment of women and the formation of a future vision to enable them. This research constitutes the intersection between the two phenomena , namely the empowerment of women and the development process.